2017
DOI: 10.1002/ece3.3617
|View full text |Cite
|
Sign up to set email alerts
|

Sampling intraspecific variability in leaf functional traits: Practical suggestions to maximize collected information

Abstract: The choice of the best sampling strategy to capture mean values of functional traits for a species/population, while maintaining information about traits’ variability and minimizing the sampling size and effort, is an open issue in functional trait ecology. Intraspecific variability (ITV) of functional traits strongly influences sampling size and effort. However, while adequate information is available about intraspecific variability between individuals (ITVBI) and among populations (ITVPOP), relatively few st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 56 publications
(114 reference statements)
1
17
0
Order By: Relevance
“…More recently, psychrometer-based estimates of leaf osmotic potential (π), followed by calculations based on known general regression models between π and TLP [28], or on corrections based on leaf dry matter content [29], have allowed for fast and reliable estimates of TLP. These new approaches are supporting the introduction of this parameter in ecological studies involving large numbers of species or samples at different spatial scales [30][31][32].…”
Section: Introductionmentioning
confidence: 84%
“…More recently, psychrometer-based estimates of leaf osmotic potential (π), followed by calculations based on known general regression models between π and TLP [28], or on corrections based on leaf dry matter content [29], have allowed for fast and reliable estimates of TLP. These new approaches are supporting the introduction of this parameter in ecological studies involving large numbers of species or samples at different spatial scales [30][31][32].…”
Section: Introductionmentioning
confidence: 84%
“…However, for broadleaf species, within-individual variation in SLA can be substantial. Petruzzellis et al [10] found that in Quercus ilex, the change in SLA related to light availability decreasing from the upper to the lower canopy and from outer to inner part of the canopy can be as much as 43% of the total intraspecific variation. SLA responds well to varying microenvironments within a forest and is directly influenced by the light intensity in the medium and large gaps compared to small gaps [21], which may partly explain the lack of directional SLA variation in the lower canopy in silver birch.…”
Section: Discussionmentioning
confidence: 99%
“…The increased interest payed to the inclusion of intraspecific variability in ecological studies raised also the question whether different spatial levels could account for different proportion of traits' variability. As an example, Petruzzellis et al (2017) compared variability patterns across multiple spatial scale of one morphological (SLA) and one physiological (leaf osmotic potential, π) functional trait in a population of Q. ilex. They found that the variability of SLA was mainly spread within individuals, while the variability of π was much higher between rather than within individuals of the same species.…”
Section: Plant Functional Traits and Intraspecific Variabilitymentioning
confidence: 99%
“…About 500 species whose traits measurements have been published in papers considered in this review are not available in TRY. Moreover, 113 species among these (8% of the Intraspecific Trait Variability, which has a strong effect on the sampling size and effort (Petruzzellis et al 2017), is still scarcely considered at population and community-level, while intraspecific variability is often considered in ecophysiological studies. Moreover, we underline the need of approaches evaluating trait-environment relationships at broad spatial and temporal scales, possibly resulting from the collaboration of several research groups at national level, as well as analysis of traits variations along ecological gradients, in order to make predictions about land use and climate change impacts.…”
Section: Conclusion and Future Research Perspectivesmentioning
confidence: 99%